1992
DOI: 10.1128/aac.36.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cefetamet (Ro 15-8074) on Treponema pallidum and experimental syphilis

Abstract: Cefetamet pivoxil (Ro 15-8075) is a newly developed, expanded-spectrum cephalosporin that is orally active.In vitro, the active form, cefetamet (Ro 15-8074),-at a concentration of 0.05 ;Lg/ml killed and lysed Treponema paUlidum. Rabbit serum did not diminish its effectiveness. The antibiotic rapidly entered the circulation following intramuscular inection into rabbits, attaining its highest levels of 24 to 37 ,ug/ml within 10 to 30 min.Animals were infected intradermally with T. paUlidum and then treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Time to resolution of clinical signs was also shorter in the azithromycin group than in the penicillin and erythromycin groups. The newer cephalosporins, i.e., cefmetazole, ceftizoxime, and cefetamet (Ro 15-8074), also show promise in animal models (14,92,188). Although useful in the treatment of other sexually transmitted diseases, quinolones have shown poor efficacy in animal models of syphilis (6,327,344).…”
Section: Newer and Experimental Agentsmentioning
confidence: 99%
“…Time to resolution of clinical signs was also shorter in the azithromycin group than in the penicillin and erythromycin groups. The newer cephalosporins, i.e., cefmetazole, ceftizoxime, and cefetamet (Ro 15-8074), also show promise in animal models (14,92,188). Although useful in the treatment of other sexually transmitted diseases, quinolones have shown poor efficacy in animal models of syphilis (6,327,344).…”
Section: Newer and Experimental Agentsmentioning
confidence: 99%
“…Penicillin remains the first choice for the treatment of syphilis till today. [7] The highest treponemicidal serum concentration of penicillin is 0.36 µg/ml which can eliminate the organism in 6-9 h. [8] Human infections with TP elicit dynamic immune reactions causing damage to the body. Several researchers have shown that T cells, B lymphocytes, NK cells, and IL-2 may participate in the pathogenesis of the spirochete.…”
Section: Introductionmentioning
confidence: 99%